Step 1

The equation for the interest earned is

\(\displaystyle{I}={P}\cdot{r}\cdot{t}\)

where I: Interest

P: Principal

r: Rate of interest

t: Time in years

Step 2

Substitute the given alues in the above expression to find the interest earned.

\(\displaystyle{P}=\${4000}\)

\(\displaystyle{r}={5}\%\)

\(\displaystyle{t}={3}\) years

\(\displaystyle{I}={P}\cdot{r}\cdot{t}\)

\(\displaystyle={4000}\times{\frac{{{5}}}{{{100}}}}\times{3}\)

\(\displaystyle={600}\)

Step 3

Answer:

The algebraic expression that gives the interest, \(\displaystyle{I}={P}{r}{t}\).

The interest obtained after 3 years \(\displaystyle=\${600}\).

The equation for the interest earned is

\(\displaystyle{I}={P}\cdot{r}\cdot{t}\)

where I: Interest

P: Principal

r: Rate of interest

t: Time in years

Step 2

Substitute the given alues in the above expression to find the interest earned.

\(\displaystyle{P}=\${4000}\)

\(\displaystyle{r}={5}\%\)

\(\displaystyle{t}={3}\) years

\(\displaystyle{I}={P}\cdot{r}\cdot{t}\)

\(\displaystyle={4000}\times{\frac{{{5}}}{{{100}}}}\times{3}\)

\(\displaystyle={600}\)

Step 3

Answer:

The algebraic expression that gives the interest, \(\displaystyle{I}={P}{r}{t}\).

The interest obtained after 3 years \(\displaystyle=\${600}\).